2018
DOI: 10.1177/0032258x18812006
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not getting them the support they need’: Exploratory research of police officers’ experiences of community mental health

Abstract: Police officers are first responders in a role which not only encompasses crime, but also increasing welfare issues. Issues have been highlighted with officers ‘detaining’ those with mental health difficulties and the impact that this process can have upon all involved. However, there appears to be a shift towards a police-health nexus. An exploratory study interviewed ten UK police officers with a view to understanding officers’ experiences of working with people with mental health difficulties and the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…Mental health crises will often take place in a person’s home with others, often family, present. In line with research of parents of children with psychosis,87 companions described the, often traumatic, impact of the FR response and a lack of inclusion and communication 18 24–30 33–37 39–41 43–60 62–70 74–78 81 82 86 88–104. Our findings reflect that of previous studies,105 which show that family/carers experience distress, guilt, reluctance to call FRs, fear of disproportionate use of force and relief for having FR support.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mental health crises will often take place in a person’s home with others, often family, present. In line with research of parents of children with psychosis,87 companions described the, often traumatic, impact of the FR response and a lack of inclusion and communication 18 24–30 33–37 39–41 43–60 62–70 74–78 81 82 86 88–104. Our findings reflect that of previous studies,105 which show that family/carers experience distress, guilt, reluctance to call FRs, fear of disproportionate use of force and relief for having FR support.…”
Section: Discussionsupporting
confidence: 89%
“…Previous reviews71–73 reported FRs’ reasons for force, such as their duty of care, bystanders and themselves, and that PMI are likely to be resistant and this would require proportionate force. FRs suggested that using force is required to gain control and central to their profession, and dealing with MHC was not, at least officially, a central part of their role 25 26 33 36 37 45 51 52 56 58 59 62 68 70 74–78. However, the role of FRs in managing mental ill health in the community is vital and likely to increase due the COVID-19 pandemic,79 the subsequent economic crisis, as well as climate change, which disproportionally affects vulnerable people and can be the cause for mental illness 80.…”
Section: Discussionmentioning
confidence: 99%